2011
DOI: 10.1159/000324850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregabalin on Subjective Sleep Disturbance Symptoms during Withdrawal from Long-Term Benzodiazepine Use

Abstract: Aim: To evaluate the effectiveness of pregabalin as a tapering therapy on the subjective sleep quality of patients who underwent a benzodiazepine withdrawal program in routine medical practice. Methods: Secondary analysis of a 12-week prospective, open noncontrolled study carried out in patients who met DSM-IV-TR criteria for benzodiazepine dependence. Sleep was evaluated with the Medical Outcomes Study Sleep Scale (MOS Sleep Scale). Results: 282 patients were included in the analysis. Mean (±SD) pregabalin do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Almost half the respondents were using benzodiazepines. Gabapentinoids have been shown to improve the impairment in sleep quality brought on by problematic benzodiazepine and alcohol use [23,24]. Although not directly referred to by the respondents, this effect may contribute to gabapentinoid abuse within this population, and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half the respondents were using benzodiazepines. Gabapentinoids have been shown to improve the impairment in sleep quality brought on by problematic benzodiazepine and alcohol use [23,24]. Although not directly referred to by the respondents, this effect may contribute to gabapentinoid abuse within this population, and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Pregabalin efficacy did not depend on the benzodiazepine that was being discontinued, or the presence of substance use disorders including opioid- and alcohol-related disorders. In a secondary analysis of the same study, pregabalin treatment led to a 55% improvement in sleep quality at study endpoint, and also improvements in sleep disturbance, snoring, shortness of breath, sleep adequacy, sleep quantity, and daytime somnolence [36]. …”
Section: Benzodiazepine and Zolpidem Withdrawal Symptomsmentioning
confidence: 99%
“…The effect of PGN on overall sleep problems was similar regardless of the BZD abused. The authors concluded that the mechanism that could be underlying the improvement in sleep measures associated to PGN could be related to its efficacy in improving anxiety symptoms [69]. PGN's tolerability was considered excellent or good in most subjects.…”
Section: Pregabalin: Pregabalin (Pgn) (S)-3-(aminomethyl)-5-methyl-mentioning
confidence: 99%